2016
DOI: 10.1002/hep.28678
|View full text |Cite
|
Sign up to set email alerts
|

A Model to predict severity of drug‐induced liver injury in humans

Abstract: Drug-induced liver injury (DILI) is a major public health concern, and improving its prediction remains an unmet challenge. Recently, we reported the Rule-of-2 (RO2) and found lipophilicity (logP 3) and daily dose 100 mg of oral medications to be associated with significant risk for DILI; however, the RO2 failed to estimate grades of DILI severity. In an effort to develop a quantitative metrics, we analyzed the association of daily dose, logP, and formation of reactive metabolites (RM) in a large set of Food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 36 publications
4
110
0
Order By: Relevance
“…Chen et al[34] combined the rule-of-two with the capacity to produce reactive metabolites and implemented a model to assess the risk of DILI onset and severity. Both dose-based and Cmax based-scores were calculated.…”
Section: Suspecting and Diagnosing Dili: A Current Dilemmamentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al[34] combined the rule-of-two with the capacity to produce reactive metabolites and implemented a model to assess the risk of DILI onset and severity. Both dose-based and Cmax based-scores were calculated.…”
Section: Suspecting and Diagnosing Dili: A Current Dilemmamentioning
confidence: 99%
“…Therefore, we applied the score developed by Chen et al[34] to DOACs and found intriguing data (Table 2). Based on these results, different issues emerge: (1) no DOAC appears to be associated with risk of severe liver damage (they all received a score well below the threshold of 7); (2) the highest score emerged for dabigatran; (3) the risk does not appear to be strongly influenced by dose or Cmax (there is only a small increase in Cmax-based score), or chemical motifs; (4) DOACs pose a lower risk as compared to warfarin (the dose-based risk score is 4.67, according to Chen et al[34]).…”
Section: A Critical Analysis Of the Dili Risk Score: The Case Of Dirementioning
confidence: 99%
See 1 more Smart Citation
“…The project has developed several predictive models 11-14 . For example, we developed a “rule-of-two” model based on the observations that oral medications of high daily dose and lipophilicity were associated with significant risk of DILI 12 ; the model identified drugs that caused severe DILI but produced a number of false negatives.…”
Section: Introductionmentioning
confidence: 99%
“…We also constructed a computational model that predicts human hepatotoxicity based on patterns of gene expression observed in rats following short-term in vivo exposures 11 . More recently, we developed a DILIScore model that is able to quantitatively assess a drug’s severity for DILI based on three sets of information (i.e., daily dose, lipophilicity, and the presence of reactive metabolites 14 . )…”
Section: Introductionmentioning
confidence: 99%